EFEKTIFITAS PENGGUNAAN METODE DISKUSI PADA LAYANAN BIMBINGAN KELOMPOK DALAM PENGEMBANGAN KETERAMPILAN KOMUNIKASI INTERPERSONAL PESERTA DIDIK (Studi Eksperimen di Kelas XI IPS1 SMA Negeri 2 Koto XI Tarusan) - Joni Adison; Suryadi Suryadi (Sekolah Tinggi Pariwisata Mataram, 2021)
This research background is student’s interpersonal communication skills are less good, the students are to be silent, can not express their opinions. The purpose of this research : 1) description of student’s interpersonal communication before implemented group guidance, 2) description of student’s interpersonal communication after implemented group guidance, 3) Effectiveness of the using discussion methods on group counseling guidance discussion toward improving students’ interpersonal communication skills.This research was quantitative research. The method used in this research was quasi experiment research design by using discussion method in group counseling guidance toward students. Sample taking was used purposive sampling technique. Quantity of sample in this research there were 10 students. Instrument used in this research was questionaire. While, technique of data analysis was used t-test technique.The result of this research revealed that: 1) description of student’s interpersonal communication before implemented group guidance was in less good criteria, 2) description of student’s interpersonal communication after implemented group guidance was in good enough criteria, 3) effectiveness of the using discussion methods on group counseling guidance discussion toward improving students’ interpersonal communication skills seen in effective criteria. Result of this research recommended to the counseling guidance teachers toward improving students’ interpersonal communication by using discussion method, because the existing of discussion method in group counseling guidance is useful toward improving students’ interpersonal communication.